First quantitative dosages: Strong correlations between non-5-HT2Rs serotonin receptors on normal human heart valves - Schussler, Olivier; Maroteaux, Luc; Jashari, Ramadan; Falcoz, Pierre; Alifano, Marco; Lecarpentier, Yves; Launay, Jean-Marie (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Although critical in development and pathology, quantitative expression of serotonin (5-HTRs) receptors in animal or human valvular tissues has never been performed. Methods: Quantification of most frequent 5-HTRs reported to be present in human peripheral tissue was performed using radiolabeled agonist/antagonist. A membrane protein extract from normal human valve (aortic/mitral/tricuspid and some pulmonary) compromised for clinics was obtained from Homograft bank. Results: We analyzed 5-HT1AR/5-HT1B/DR/5-HT2AR/5-HT2BR/5-HT2CR/5-HT4R/5-HT7R on 28 hearts. We confirmed the tissue quantitative content for respective proteins in femtomol/mg of protein extracts: for 5-HT2AR (35.9+/-0.7), 5-HT2BR (28.8+/-1.3) but also robust expression for 5-HT4R (38+/-4.2). We identified one 5-HT1ARs (4.9+/-0.3) and the possible expression but at a very low level if present of previous reported 5-HT1B/DRs (1.3+/-0.5) but also 5-HT7Rs (3.5+/0.1) and 5-HT2CRs (1.2+/-0.1). Interestingly, by univariate analysis we observed many correlations between the different 5-HTRs quantitative levels, especially between 5-HT1AR/5-HT1B/DR/5-HT4R/5-HT7R. The strongest correlations were observed between 5-HT1AR/5-HT1B/DR and between 5-HT4R/5-HT7R but no correlation between 5-HT2AR/5-HT2BR. By multivariate analyses for a specific 5-HTRs level of expression after adjustment for sites and other 5-HTR’s: 5-HT1AR was correlated with 5-HT1B/DR; 5-HT4R with 5-HT7R and 5-HT1AR; 5-HT2BR with 5-HT2AR only. No correlation for 5-HT2C was observed. Conclusion: 5-HT2AR/5-HT2BR and the new non 5-HT2Rs (i.e. 5-HT4R) are equally expressed on human valves and also some of 5-HT1AR. Since these non 5-HT2Rs are coupled to different G-proteins, they might control cAMP levels in an opposite fashion. The regulation of non 5-HT2Rs and possible subsequent cAMP signaling may be theoretically an interesting mean to control the main 5-HT2Rs signaling (i.e. PLC/DAG-PKC-ERK/Ras/Src signaling) that is involve in valvular fibrosis and degeneration.